1996
DOI: 10.1128/mcb.16.4.1335
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclin-Dependent Kinase Inhibitor p21WAF1 Is Required for Survival of Differentiating Neuroblastoma Cells

Abstract: We are employing recent advances in the understanding of the cell cycle to study the inverse relationship between proliferation and neuronal differentiation. Nerve growth factor and aphidicolin, an inhibitor of DNA polymerases, synergistically induce neuronal differentiation of SH-SY5Y neuroblastoma cells and the expression of p21 WAF1, an inhibitor of cyclin-dependent kinases. The differentiated cells continue to express p21 WAF1 , even after removal of aphidicolin from the culture medium. The p21 WAF1 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
4

Year Published

1997
1997
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(151 citation statements)
references
References 48 publications
6
141
4
Order By: Relevance
“…This argues in favor of a repressor role for p21 in inhibiting paclitaxel-induced apoptosis mediated by p34 cdc2 . Several studies have shown that p21 acts as a survival factor (Poluha et al, 1996;Polyak et al, 1996;Waldman et al, 1996;Wang and Walsh, 1996). We found that inhibition of p21 expression using a p21 antisense oligonucleotide led to a signi®cant increase in paclitaxel cytotoxicity in MCF-7 cells.…”
Section: In¯uence Of Antisense-p21 On Cell Survival After Paclitaxel mentioning
confidence: 99%
“…This argues in favor of a repressor role for p21 in inhibiting paclitaxel-induced apoptosis mediated by p34 cdc2 . Several studies have shown that p21 acts as a survival factor (Poluha et al, 1996;Polyak et al, 1996;Waldman et al, 1996;Wang and Walsh, 1996). We found that inhibition of p21 expression using a p21 antisense oligonucleotide led to a signi®cant increase in paclitaxel cytotoxicity in MCF-7 cells.…”
Section: In¯uence Of Antisense-p21 On Cell Survival After Paclitaxel mentioning
confidence: 99%
“…It was initially shown to increase during DNA damage induced cell death (El-Deiry et al, 1994). More recently, it has been shown that inducing p21 can decrease apoptosis in di erentiating muscle cell lines (Wang and Walsh, 1996) and prostaglandin treated colon carcinoma cell lines (Gorospe et al, 1996), while decreasing expression during di erentiation of a neuronal line increases apoptosis (Poluha et al, 1996). p21 has also been demonstrated to inhibit two members of the stress activated protein kinase family (SAPK), JNK and p38 (Shim et al, 1996), proteins thought to be involved in the signalling pathways leading to cell death in response to stress (Davis, 1994;.…”
Section: Introductionmentioning
confidence: 99%
“…Since p27 has been shown to confer resistance against anticancer agents to tumor cells (Croix et al, 1996), it appeared likely that p27 has antiapoptotic activity similar to other cdk inhibitors such as p16 and p21 (Wang and Walsh, 1996;Poluha et al, 1996). We therefore hypothesized that c-Myc may mediate apoptosis through the down-regulation of p27, and that Pim-1 might facilitate this process.…”
Section: Pim-1 Stimulates Rather Than Inhibits C-myc-mediated Apoptosismentioning
confidence: 99%